2016
DOI: 10.1111/ajgw.12220
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of deficit and partial root-zone drying irrigation techniques using moderately saline water on ion partitioning in Shiraz and Grenache grapevines

Abstract: Background and Aims: Deficit irrigation techniques have been used to improve water use efficiency and control vigour in grapevines, but the consequences of using saline water with these techniques have been little investigated. Here, we investigate the effect of deficit irrigation with moderately saline water on within-vine ion allocation. Methods and Results: Drip-irrigated own-rooted Shiraz and Grenache vines grown in pots were subjected to control, reduced control and partial root-zone drying (both approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…However, water quality, mainly in regards of a too high salt concentration, inducing salt stress, can have detrimental effects on overall vineyard performance (Costa et al, 2016;Laurenson et al, 2012), more specifically on vine transpiration (Pereira et al, 2015) and can negatively affect yield and berry composition and consequently final wine quality (Miras-Avalos and Intrigliolo, 2017). Using moderately saline water for deficit irrigation, Degaris et al (2016) reported an effect on ion partitioning (Cl -, Na + , and K + ) in grapevines berries.…”
Section: Towards a Site-specific Deficit Irrigation Strategy?mentioning
confidence: 99%
“…However, water quality, mainly in regards of a too high salt concentration, inducing salt stress, can have detrimental effects on overall vineyard performance (Costa et al, 2016;Laurenson et al, 2012), more specifically on vine transpiration (Pereira et al, 2015) and can negatively affect yield and berry composition and consequently final wine quality (Miras-Avalos and Intrigliolo, 2017). Using moderately saline water for deficit irrigation, Degaris et al (2016) reported an effect on ion partitioning (Cl -, Na + , and K + ) in grapevines berries.…”
Section: Towards a Site-specific Deficit Irrigation Strategy?mentioning
confidence: 99%
“…The fruit harbor most of the K + within the grapevine ( Pradubsuk and Davenport, 2010 ; Degaris et al, 2016 ). K + accumulation into the berry is a function of availability and uptake by roots from the soil ( Ruhl, 1989 ; Wang et al, 2010 ), the extent of K + redistribution from leaves ( Coombe, 1992 ) and mobilization from storage sinks within the woody structures of the vine ( Conradie, 1981 ; Williams and Biscay, 1991 ).…”
Section: Long Distance Transport Of K +mentioning
confidence: 99%
“…Interestingly, saline irrigation caused small variations in juice Brix, titratable acidity, pH, and malate concentration. Recently, Degaris et al (2016) proved that ion partitioning in grapevines and thus Cl - , Na + , and K + in berries and juice depends on the type of deficit irrigation applied in two red cultivars (Shiraz and Grenache). Partial root-zone drying reduced the concentration of these ions in the fruit of both cultivars when compared with a fully irrigated control and a deficit irrigated treatment.…”
Section: Saline Stressmentioning
confidence: 99%